Distinct Shift in Beta-Cell Glutaredoxin 5 Expression Is Mediated by Hypoxia and Lipotoxicity Both In Vivo and In Vitro - Petry, Sebastian Friedrich; Sun, Lia Mingzhe; Knapp, Anna; Reinl, Sabrina; Linn, Thomas (Frontiers in Endocrinology, 2018)
Histomorphological and functional alterations in pancreatic islet composition directly correlate with hyperglycemia severity. Progressive deterioration of metabolic control in subjects suffering from type 2 diabetes is predominantly caused by impaired beta-cell functionality. The glutaredoxin system is supposed to wield protective properties for beta-cells. Therefore, we sought to identify a correlation between the structural changes observed in diabetic pancreatic islets with altered glutaredoxin 5 expression, in order to determine an underlying mechanism of betacell impairment. Islets of db/db mice presenting with uncontrolled diabetes were assessed in terms of morphological structure and insulin, glucagon, and glutaredoxin 5 expression. MIN6 cell function and glutaredoxin 5 expression were analyzed after exposure to oleic acid and hypoxia. Islets of diabese mice presented with typical remodeling and were marked by distinct reduction of, and shifts, in localization of glutaredoxin 5-positive cells. These islets featured decreased glutaredoxin 5 as well as insulin and glucagon content. In beta-cell culture, glutaredoxin 5 protein and mRNA expression were decreased by hypoxia and oleic acid but not by leptin treatment. Our study demonstrates that glutaredoxin 5 expression patterns are distinctively altered in islets of rodents presenting with uncontrolled diabesity. In vitro, reduction of islet-cell glutaredoxin 5 expression was mediated by hypoxia and oleic acid. Thus, glutaredoxin 5-deficiency in islets during diabetes may be caused by lipotoxicity and hypoxia.